Kedudukan Pengaduan Konstitusional dalam Sistem Kekuasaan Kehakiman Menurut UUD 1945 - Syaiful Bahari; La Ode Mbunai; Muhammad Panca Prana Mustaqim Sinaga; Tuti Elawati (JUSTLAW : Journal Science and Theory of law, 2025)
Since the 1998 reform, the Indonesian state system has changed a lot, especially after the amendment of the 1945 Constitution. One of the amendments was the Judicial Power. Previously, the Indonesian state system did not recognize constitutional review. There was no mechanism for constitutional review of laws against the 1945 Constitution, because laws were the full authority of the Legislative and the President and could not be sued except through a legislative review mechanism. In the third amendment of the 1945 Constitution, the mechanism for constitutional review of laws against the 1945 Constitution was opened and a new institution was formed, namely the Constitutional Court. In theory and constitutional practice in various countries, the authority of the Constitutional Court is not only judicial review of laws against the 1945 Constitution, but also includes all constitutional review practices, both laws and regulations under the Law and actions of branches of power that are considered to violate or contradict the 1945 Constitution. Unfortunately, the practice of constitutional review as a whole has still not been accepted by the MPR and lawmakers. As a result, until now there has been dualism in the constitutional review carried out by the Constitutional Court. Meanwhile, related to constitutional review through the Constitutional Complaint mechanism, it has not yet found a place in the Indonesian state system. This study uses a legislative approach and a historical approach. The study through the legislative approach focuses on the formation of new legal norms and the historical study explains the process and background of the formation of legal institutions.